Hubungan Antara Kecerdasan Emosi Dan Pengetahuan Tentang Abk Dengan Kompetensi Guru Di Sekolah Inklusif - Sa'idah, Muyasarotun, Taufik Kasturi, S.Psi., M.Si., Ph.D (2014)
This research is aimed to investigate the relationship between emotional intelligence and knowledge of special need children with the competence of teachers in inclusive schools. The hypothesis of this study is that there is a relationship between emotional intelligence and knowledge of special need children with the competence of teachers in inclusive school. This study is a quantitative correlation approach. The population was 46 teachers at the Islamic elementary school Nidaul Salatiga. The results showed that there is a significant positive relationship between emotional intelligence and competence of teachers in inclusive school indicated by the value of the correlation coefficient rx1y is 0.661 with a significance p = 0.000 <p = 0,01 and effective contribution emotional intelligence to the competencies of teachers in inclusive schools amounted to 43.831%. Theoretical knowledge of special need children proved to have no effect on the competence of teachers in inclusive schools, as indicated by the value of the correlation of rx2y is -0.166 with a significance p = 0.136> p = 0.01 and effective contribution knowledge of special need children to the competence of teachers in inclusive schools -0.231%. Teachers in SDIT Nidaul Hikmah Salatiga have a high level of competence with the empirical mean of 142,6304 higher than hypothetical mean of 120, also have a high level of emotional intelligence with the empirical mean of 94,0870 higher than the hypothetical mean of 75, while the level of knowledge about ABK was moderate with empirical mean of 11.8043 is only slightly higher than the hypothetical mean of 11,5. Competence of teachers in inclusive schools can be improved by improving the emotional intelligence and applicable knowledge of special need children that is the experience of teachers interact with children with special needs